A randomized controlled trial undertaken to test a nurse‐led weight management and exercise intervention designed for people with serious mental illness who take second generation antipsychotics. (14th September 2012) - Usher, Kim; Park, Tanya; Foster, Kim; Buettner, Petra
Abstract Aim To test the effect of a nurse‐led intervention on weight gain in people with serious mental illness prescribed and taking second generation antipsychotic medication. Background Weight gain and obesity has reached epidemic proportions in the general population with the prevalence of Metabolic Syndrome reaching 20–25% of the global population. People with serious mental illness are at even higher risk, particularly those taking second generation antipsychotic medication. Design An experimental randomized controlled trial was undertaken. Method The control group received a 12‐week healthy lifestyle booklet. In addition to the booklet, the intervention group received weekly nutrition and exercise education, exercise sessions, and nurse support. Participants (n = 101) were assessed at baseline and 12 weeks. Data were collected between March 2008–December 2010. Seven outcome measures were used: body measurements included girth (cm), weight (kg), height (cm), and body mass index (kg/m2); questionnaires included the medication compliance questionnaire, the Drug Attitude Inventory, the Liverpool University Neuroleptic Side Effect Rating Scale, and the Medical Outcomes Study Short Form 36. Differences in primary outcome measures between baseline and 12 weeks follow‐up were compared between intervention and control groups using standard bi‐variate statistical tests. The study was conducted between 2008–2010. Results The analysis of outcome measures for the control group (n = 50) and intervention group (n = 51) was not statistically significant. There was a mean weight change of −0·74 kg at 12 weeks for the intervention group (n = 51), while the control group (n = 50) had a mean weight change of −0·17 kg at 12 weeks. Conclusion The results were not statistically significant.